(untitled) (Swiss Medical Weekly, 2023)
AIM OF THE STUDY: The first and second waves of the COVID-19 pandemic led to a tremendous burden of disease and influenced several policy directives, prevention and treatment strategies as well as lifestyle and social behaviours. We aimed to describe trends of hospitalisations with COVID-19 and hospital-associated outcomes in these patients during the first two pandemic waves in Switzerland. METHODS: In this nationwide retrospective cohort study, we used in-hospital claims data of patients hospitalised with COVID-19 in Switzerland between January 1st and December 31st, 2020. First, stratified by wave (first wave: January to May, second wave: June to December), we estimated incidence rates (IR) and rate differences (RD) per 10,000 person-years of COVID-19-related hospitalisations across different age groups (0–9, 10–19, 20–49, 50–69, and ≥70 years). IR was calculated by counting the number of COVID-19 hospitalisations for each patient age stratum paired with the number of persons living in Switzerland during the specific wave period. Second, adjusted odds ratios (aOR) of outcomes among COVID-19 hospitalisations were calculated to assess the association between COVID-19 wave and outcomes, adjusted for potential confounders. RESULTS: Of 36,517 hospitalisations with COVID-19, 8,862 (24.3%) were identified during the first and 27,655 (75.7%) during the second wave. IR for hospitalisations with COVID-19 was highest during the second wave and among patients above 50 years (50–69 years: first wave: 31.49 per 10,000 person-years; second wave: 62.81 per 10,000 person-years; RD 31.32 [95% confidence interval [CI]: 29.56 to 33.08] per 10,000 person-years; IRR 1.99 [95% CI: 1.91 to 2.08]; ≥70 years: first wave: 88.59 per 10,000 person-years; second wave: 228.41 per 10,000 person-years; RD 139.83 [95% CI: 135.42 to 144.23] per 10,000 person-years; IRR 2.58 [95% CI: 2.49 to 2.67]). While there was no difference in hospital readmission, when compared with the first wave, patients hospitalised during the second wave had a lower probability of death (aOR 0.88 [95% CI: 0.81 to 0.95], ARDS (aOR 0.56 [95% CI: 0.51 to 0.61]), ICU admission (aOR 0.66 [95% CI: 0.61 to 0.70]), and need for ECMO (aOR 0.60 [95% CI: 0.38 to 0.92]). LOS was –16.1 % (95% CI: –17.8 to –14.2) shorter during the second wave. CONCLUSION: In this nationwide cohort study, rates of hospitalisations with COVID-19 were highest among adults older than 50 years and during the second wave. Except for hospital readmission, the likelihood of adverse outcomes was lower during the second pandemic wave, which may be explained by advances in the understanding of the disease and improved treatment options.